Plasma sarcosine does not distinguish early and advanced stages of prostate cancer - Bohm, L.; Serafin, A. M.; Fernandez, P.; Van der Watt, G.; Bouic, P. J. D.; Harvey, J. (Health and Medical Publishing Group (HMPG), 2012)
The original publication is available at http://www.samj.org.za